Aesthetic Theory and the Philosophy of Nature - Said Mikki (Philosophies, 2021)
We investigate the fundamental relationship between philosophical aesthetics and the philosophy of nature, arguing for a position in which the latter encompasses the former. Two traditions are set against each other, one is natural aesthetics, whose covering philosophy is Idealism, and the other is the aesthetics of nature, the position defended in this article, with the general program of a comprehensive philosophy of nature as its covering theory. Our approach is philosophical, operating within the framework of the ontology of the process of the production of art, inspired especially by the views of Antonin Artaud, Nietzsche, Heidegger, Bakhtin, Deleuze, and Guattari. We interrogate Dilthey and Worringer while outlining an ontology of art based on the production of nonhuman images and a nonpersonal experiential field of nature.